Respons Positif Teologi Kristen Protestan terhadap Sekularisasi Di Dunia Barat Modern - Mohammad Nuh Hasan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2022)
This article discusses how Protestant Christian theology responds to the strengthening of the secularization phenomenon. The positive response with various styles of theological reflection illustrates that the Protestant Christian theology figures above, starting from Karl Barth, Rudolf Bultmann, Dietrich Bonhoeffer and Paul Tillich, are the efforts of theologians to try to bridge the gap or gap in cultural rationality between the cultures of the classical era in where the texts of the scriptures were written with modern Western culture today. These theologians include those who give a positive response in dealing with the phenomenon of secularization in the West. However, their response actually has a style that is more or less different in their way of thinking. Although Karl Barth proposed an advanced mode of reflection, he was still bound by his orthodoxy, so that he was nicknamed